La stima dei fabbisogni irrigui a scala aziendale e consortile mediante tecniche di Osservazione della Terra - Altobelli, Filiberto; Lupia, Flavio; Vanino, Silvia; Mandarian, Iraj; Nino, Pasquale; De Michele, Carlo; Vuolo, Francesco; Natalizio, Massimo (GEOmedia, 2012)
Le applicazioni agrometeorologiche per la gestione delle colture in pieno campo e l'utilizzo di nuove tecnologie di monitoraggio sono sempre più diffuse e si concretizzano anche attraverso lo sviluppo di progetti di ricerca internazionali orientati all'implementazione di servizi operativi. Particolare rilevanza assume il programma Global Monitoring for Enviroment and Security (GMES), che supporta lo sviluppo di capacità e servizi di monitoraggio globale attraverso tecniche di Osservazione della Terra. Irrigation needs estimation at farm and district level by Earth Observation techniques SIRIUS (Sustainable Irrigation water management and River-basin governance: Implementing User-driven Services) is a research project funded by EU FP7 in the GMES framework supporting the development of monitoring services through remote sensing and ICT technologies to deliver the service to the final users. SIRIUS is developing efficient water resource management services in support of food production in water-scarce environments. It addresses water governance and management in accordance with the vision of bridging and integrating sustainable development and economic competi-tiveness. The project is developing new services for water man-agers and food producers, and a range of additional information products in support of sustainable irrigation water use and management under conditions of water scarcity and drought.